Proceedings of the Oxford University Computing Laboratory Programming Research Group Student Conference '06 - Xie, Y (Oxford University Computing Laboratory, 2006)
Program Chair:Yong Xie, Organizational Chair: Mila Katzarova, Steering Committee Chair: Tom Melham and Duncan Coutts The annual student conference of the Programming Research Group (PRG) at the Oxford University Computing Laboratory has been a forum for the presentation of some of the DPhil students' work that they have recently been doing. The 16 abstracts in this volume were presented at the PRG student conference '06, held on October 13, 2006 in the Griffiths Room at Keble College. In addition to the students' presentations, the conference also featured an invited talk by Prof. Tom Melham (Director of Graduate Studies), as well as brief announcements of two posters.